Mini-Project Based Approach to Promote Entrepreneurship and Innovation in Engineering Education - Padma, M. C.; Sridhar, V. (Journal of Engineering Education Transformations, 2016)
The tremendous changes in the world present both challenges and opportunities to the engineering education. Engineering students appear to be very well suited to become entrepreneurs. Economic trends and changes in the way employers organize and make decisions have led to an increased awareness of the potential value of entrepreneurship education to engineering students. In recent decades, there is a great demand for engineers who can literally build the future by developing innovative and cutting edge technologies that solve global problems and enhance the quality of life. For developing countries like India, it is necessary to promote entrepreneurship and innovation in the field of engineering education. Hence, modern engineers need to be entrepreneurial in order to understand and contribute in the context of market and business pressures. In this paper, we have presented two case studies taken up by a set of students and demonstrated how students are influenced to use entrepreneurial and innovative skills to develop software solutions for real life problems. From this study, it is observed that by introducing the concept of mini-project to solve a realistic problem, at least a couple of students can be motivated to become successful entrepreneurs in future.